Advanced diagnostic imaging and intervention in tendon diseases - Bruno, Federico; Palumbo, Pierpaolo; Arrigoni, Francesco; Mariani, Silvia; Aringhieri, Giacomo; Carotti, Marina; Natella, Raffaele; Zappia, Marcello; Cipriani, Paola; Giacomelli, Roberto; Di Cesare, Ernesto; Splendiani, Alessandra; et al. (Acta Biomedica Atenei Parmensis, 2020)
Degenerative tendon pathology represents one of the most frequent and disabling musculoskeletal disorders. Diagnostic radiology plays a fundamental role in the clinical evaluation of tendon pathologies. Moreover, several minimally invasive treatments can be performed under imaging guidance to treat tendon disorders, maximizing the efficacy and reducing procedural complications. In this review article we describe the most relevant diagnostic features of conventional and advanced US and MRI imaging in tendon disorders, along with the main options for image-guided intervention.